Preparation, characterization, and catalytic activity of core/shell Fe3O4polyaniline@au nanocomposites - Xuan, Shouhu (Langmuir : the ACS journal of surfaces and colloids, 2009)
We report a new method to synthesize magnetically responsive Fe3O4polyaniline@Au nanocomposites. The superparamagnetic Fe3O4@polyaniline with well-defined core/shell nanostructure has been synthesized via an ultrasound-assisted in situ surface polymerization method. The negatively charged Au nanoparticles with a diameter of about 4 nm have been effectively assembled onto the positively charged surface of the as-synthesized Fe3O4@polyaniline core/shell microspheres via electrostatic attraction. The morphology, phase composition, and crystallinity of the as-prepared nanocomposites have been characterized by transmission electron microscopy (TEM) and powder X-ray diffraction (XRD). The central Fe3O4 cores are superparamagnetic at room temperature with strong magnetic response to externally applied magnetic field, thus providing a convenient means for separating the nanocomposite from solution. As-prepared inorganic/organic nanocomposite can be used as a magnetically recoverable nanocatalyst for the reduction of a selected substrate